THE PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT DI KECAMATAN BIRINGKANAYA KOTA MAKASSAR - Yosi Glodia Tangdiaga; Frida Chairunisa; Gina Lucita (Politeknik STIA LAN Makassar, 2021)
Service quality is the quality that indicates the good or bad level of a type of service from government (sector public) to individuals who can provide positive feedback, namely community satisfaction. The aim of this research is to know partially and simultaneously the effect of service quality (care and concern, spontaneity, problem solving dan service recovery) on community satisfaction in Biringkanaya district; and knowing the dimensions of service quality (care and concern, spontaneity, problem solving dan service recovery) that have the most dominant influence on community satisfaction in Biringkanaya district. The research method used is descriptive quantitative method. The design used was cross sectional. The number of samples is 100 repondents who were determined by probability sampling technique with stratified proportional sampling, which means that the sampling was first grouped into several population soup (each sub-district) so that each sub population would have its own sample member. Data collection using a questionnaire. Data analysis using multiple linear regression analysis with partial and simultaneous hypothesis testing. The results showed that care and concern, spontaneity, problem solving dan service recovery had a positive and significant effect on community satisfaction. The means that community satisfaction is influenced by care and concern, spontaneity, problem solving dan service recovery, the rest is influenced by other factors not examined un this study.